Study and Design Analysis of Hazard Removal and Reinforcement Scheme of a Bridge Diversion Sluice - Xue Yang; Hongmei Liu; Zuojun Ning; Heng Zhang; Houjie Gong; SangSook Park; Huancheng Dong; Dali Zhang; Hefeng Zhu; Xinrong Du; Runkai Wang (Advances in Civil Engineering)
Most of the existing sluices in China have been in operation for more than 40 years, and the aging problem is becoming increasingly prominent. The selection of reinforcement schemes for sluices in vulnerable conditions is of great significance to the whole project. A reasonable reinforcement scheme can ensure their safe operation and reduce unnecessary resource investment. This study focuses on the diversion gate of a bridge in China that through aging has emerged insufficient capacity of downstream energy dissipation and scour prevention, severe scour of the diversion dike foundation, and insufficient flood control and rescue capacity. Two reinforcement schemes are examined by analyzing the engineering parameters of the bridge diversion sluice and the necessity of engineering construction, namely, raising the flood discharge level and increasing the width of the overflow section. In this study, Super Decisions software was first used to simulate the reinforcement scheme of the bridge diversion sluice, calculate the weight of the factors, and obtain the optimization scheme from the two aforementioned reinforcement schemes, which was based on the analytic network process (ANP), and the related factors affecting the reinforcement scheme of the bridge diversion sluice are determined and evaluated. The relevant calculation and analyses of the optimization scheme are conducted using ANSYS finite-element software. The selection process of reinforcement scheme for such sluices provides a reference for other similar projects.